2012
DOI: 10.1371/journal.pone.0047429
|View full text |Cite
|
Sign up to set email alerts
|

Developing Neurons Form Transient Nanotubes Facilitating Electrical Coupling and Calcium Signaling with Distant Astrocytes

Abstract: Despite the well-documented cooperation between neurons and astrocytes little is known as to how these interactions are initiated. We show here by differential interference contrast microscopy that immature hippocampal neurons generated short protrusions towards astrocytes resulting in tunneling nanotube (TNT) formation with an average lifetime of 15 minutes. Fluorescence microscopy revealed that all TNTs between the two cell types contained microtubules but 35% of them were F-actin negative. Immunolabeling ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
94
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(97 citation statements)
references
References 42 publications
2
94
0
1
Order By: Relevance
“…A model of calcium diffusion alone through TNTs was therefore not supported. Instead, the findings indicated a local influx of calcium ions into neurons through activated low-voltage calcium channels which open at low depolarization thresholds [111]. It may be that VT via ATP and glutamate released from astrocytes in development is not as effective in producing depolarization and increasing neuronal calcium signalling via purinoceptors and NMDA receptors, respectively.…”
Section: (C) Astrocyte -Neuron Crosstalk In Developmentmentioning
confidence: 92%
See 1 more Smart Citation
“…A model of calcium diffusion alone through TNTs was therefore not supported. Instead, the findings indicated a local influx of calcium ions into neurons through activated low-voltage calcium channels which open at low depolarization thresholds [111]. It may be that VT via ATP and glutamate released from astrocytes in development is not as effective in producing depolarization and increasing neuronal calcium signalling via purinoceptors and NMDA receptors, respectively.…”
Section: (C) Astrocyte -Neuron Crosstalk In Developmentmentioning
confidence: 92%
“…Developing hippocampal neurons were demonstrated to form transient nanotubes with distant astrocytes [107,111]. TNTs were found to mediate both transient calcium signals and depolarization from distant astrocytes to neurons within a limited maturation period.…”
Section: (C) Astrocyte -Neuron Crosstalk In Developmentmentioning
confidence: 99%
“…F-actins but not microtubules are found in all MNTs connecting cells such as PC12 cells or myeloid cells [4]. Although F-actin is considered as the hallmark of MNTs, some reports indicated that not all MNTs between immature hippocampal neurons and astrocytes contain F-actin, and more interestingly, F-actin-lacking MNTs were longer than those containing F-actin [14] .…”
Section: Components Of Mntsmentioning
confidence: 99%
“…Finally, the most prevailing species of free radicals within a cell are radical oxygen species (ROS and hydroxyl radicals) and radicals formed by nitric oxide (NO) [57]. The lifetime of a free radical is varying dramatically -less than a nanosecond till 3-5 s in NO [57].…”
Section: Equivalent Counterpart In the Organism?mentioning
confidence: 99%
“…The lifetime of a free radical is varying dramatically -less than a nanosecond till 3-5 s in NO [57]. The radical pair phenomenon (NO, ROS) can thus interfere with endogenous oscillations in cell or metabolic systems.…”
Section: Equivalent Counterpart In the Organism?mentioning
confidence: 99%